Razão e normatividade : Adorno, Habermas e o problema da fundamentação - Santos, Jéverton Soares dos (2015)
This research deals with a central question in philosophy: the problem of foundation. Although the concept of philosophical foundation has undergone profound transformations throughout history, it including the loss of their metaphysical, ontological and theological references, the underlying question to the theme remains the same: the search for rational grounds legitimating of thought and action. After the "Copernican turn" in philosophy undertaken by Kant and the pragmatic-linguistic turn in contemporary philosophy the question of foundation can to express as way follows: what is the transcendental element that is the practical attitude of human? In order to answer this question we will concentrate on the analysis of the thought of two great philosophers of contemporary: Theodor Adorno and Jürgen Habermas. In the meantime, we are dedicated to also examine the concept of rationality of each of these authors, as well as its normative statement of proposals of ethics. We wonder what is the model of reason more apt to examine the normative nature of issues and gnostic of our time, marked on the one hand, the technical prestige and technological sciences, which causes an instrumental view prevails human, on the other hand, often by perniciosa- influenced the mass media, which together with the deficit in the educational and cultural level prevents the full realization of the concept of majority (Mündigkeit) as telos of individual and collective life as the promised Enlightenment. Our thesis is that dialectical reason developed by Adorno presents itself as a more comprehensive and effective proposal to equate these and other issues of our historic time.